Cloning, Secretory Expression and Characterization of a Unique pH-Stable and Cold-Adapted Alginate Lyase - Wang, Zhi-Peng; Cao, Min; Li, Bing; Ji, Xiao-Feng; Zhang, Xin-Yue; Zhang, Yue-Qi; Wang, Hai-Ying (Marine drugs, 2020)
Cold-adapted alginate lyases have unique advantages for alginate oligosaccharide (AOS) preparation and brown seaweed processing. Robust and cold-adapted alginate lyases are urgently needed for industrial applications. In this study, a cold-adapted alginate lyase-producing strain Vibrio sp. W2 was screened. Then, the gene ALYW201 was cloned from Vibrio sp. W2 and expressed in a food-grade host, Yarrowia lipolytica. The secreted Alyw201 showed the activity of 64.2 U/mL, with a molecular weight of approximate 38.0 kDa, and a specific activity of 876.4 U/mg. Alyw201 performed the highest activity at 30 °C, and more than 80% activity at 25–40 °C. Furthermore, more than 70% of the activity was obtained in a broad pH range of 5.0–10.0. Alyw201 was also NaCl-independent and salt-tolerant. The degraded product was that of the oligosaccharides of DP (Degree of polymerization) 2–6. Due to its robustness and its unique pH-stable property, Alyw201 can be an efficient tool for industrial production.